Gender Differences in Adolescents' Socioemotional Development and Their Later Economic Consequences - Ghazala Azmat; Katja Maria Kaufmann; Yasemin Özdemir (Institute of Labor Economics (IZA), 2022)
We exploit a large exogenous shock to study socioemotional development (SED) during adolescence and the consequences on relevant economic outcomes, focusing on gender differences. Using novel, longitudinal, microdata on cohorts of East German adolescents before and after a large macro shock (the German Reunification), we causally estimate the impact on SED, finding substantial negative effects in the short run. These effects are similar for male and female youth. In terms of how these changes in SED impact behavior, however, we find stark differences by gender, observing important changes in externalizing behavior and behavioral control problems among males only as opposed to changes in internalizing behavior among females only. Ultimately, the effects on longer-run outcomes (subjective health, wellbeing, education) are grave and similar for both genders
Keywords: D91; I12; I31; J13; J16; J24; 330; socioemotional development; youths; gender; behavior; health; education